What is the Identity of Interdisciplinarity? - Lange, Michael (Journal of Interdisciplinary Studies in Education, 2019)
Interdisciplinarity is nothing new. The earliest attempts to understand, organize, or codify knowledge and learning were infused with what today look like interdisciplinary thinking and approaches. Indeed, interdisciplinarity only makes sense if it is preceded by some system of disciplines that perceive themselves and/or are perceived to be separable and bounded. There have to be lines to transcend, categories to move between, before something can be “inter-” anything. So to call the education of philosopher kings in Republic interdisciplinary is a bit anachronistic, as the current forms of interdisciplinarity are rooted in the post-Enlightenment and modern divisions within academia, well post-dating Plato. It was in that post-Enlightenment moment when disciplinary beliefs and practices made the biggest leap toward becoming disciplinary identities as well.